More than a belated Gutenberg Age: Daily Newspapers in India: An Overview of the Print Media Development since the 1980s, Key Issues and Current Perspectives - Schneider, Nadja-Christina (Global Media Journal - German Edition, 2013)
While TV may still be the dominant medium in India today, and the internet and mobile phone industry are currently growing at a tremendous speed, ‘old’ media such as the press don’t seem to be losing ground as yet. In times of a recurrent debate about the crisis of print media in Europe and the US, the Indian newspaper market still keeps growing and has attracted the interest of multinational corporations. One reason for this is that India is presently one of the largest markets for English-language newspapers and magazines in the world. Notwithstanding the continued growth of the English-language press, it is above all daily newspapers in the major Indian languages which form the motor of this unprecedented press boom. The article shows that in the wake of economic liberalization and the enforcement of the consumption-oriented market economy, the newspaper market in India can be said to be changing from a linguistically ‘split public’, which was characterized by many asymmetries for decades, to an integrated multilingual ‘consumer sphere’. It can thus be argued that in this new consumer sphere, the old existing and imaginary boundaries between ‘English-language’, ‘Indian-language’ or ‘regional newspapers’ are becoming increasingly fuzzy, whereas the new geographies of the ‘regional’ are now very important for the expansion and consolidation of daily newspapers. In order to de-westernize the current debate about the ‘newspaper crisis’, it would thus be important to look at different historical as well as contemporary trajectories of newspaper developments in the framework of changing media configurations in the so-called global South, which may differ significantly from the European or North American context.